1995
DOI: 10.3109/00048679509064986
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia, Convulsions and Neuroleptic Malignant Syndrome in a Male with Schizoaffective Disorder

Abstract: Hyponatremia and NMS have been found to be associated. This association may be due to an undefined common pathogenesis, or may be coincidental. Hyponatremia may also hinder the diagnosis of NMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…16 Indeed, in a 6-year follow-up of 274 elderly participants (36 with diabetes and 238 without diabetes), Hassing et al 17 found type 2 diabetes to be associated with accelerated cognitive decline in old age that may result in dementia. It seems that type-2 diabetes is an independent risk factor for cognitive decline and dementia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Indeed, in a 6-year follow-up of 274 elderly participants (36 with diabetes and 238 without diabetes), Hassing et al 17 found type 2 diabetes to be associated with accelerated cognitive decline in old age that may result in dementia. It seems that type-2 diabetes is an independent risk factor for cognitive decline and dementia.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The elevation of creatine kinase was nonspecific and does not confirm the diagnosis of NMS. 1,2,17,18 It follows that patients who sustain basal ganglia damage associated with EPM after hyponatremia and who are also receiving SGAs could be at increased risk of developing NMS. 4,5 She received quetiapine for 2 years without incident and previously received more potent antipsychotics without NMS.…”
Section: Discussionmentioning
confidence: 99%
“…(100) on December 21, 2021 by guest. Protected by copyright.http://bmjopen.bmj.com/ BMJ Open: first published as 10.1136/bmjopen-2020-046539 on 9 December 2021.…”
mentioning
confidence: 99%
“…Water intoxication is often complicated with hyponatremia and hypo osmotic pressure, and is reported to be associated with SIADH (11). There are few case reports showing complication of NMS and water intoxication (5,(12)(13)(14)(15)(16)(17). Moreover, rhabdomyolysis is sometimes complicated together with both NMS and water intoxication (12,14,18).…”
Section: Discussionmentioning
confidence: 99%